2015
DOI: 10.4171/jst/90
|View full text |Cite
|
Sign up to set email alerts
|

On the completeness and Riesz basis property of root subspaces of boundary value problems for first order systems and applications

Abstract: Abstract. The paper is concerned with the completeness property of root functions of general boundary value problems for n × n first order systems of ordinary differential equations on a finite interval. In comparison with the recent paper [45] we substantially relax the assumptions on boundary conditions guarantying the completeness of root vectors, allowing them to be nonweakly regular and even degenerate. Emphasize that in this case the completeness property substantially depends on the values of a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…There are many results about the determinants for different classes of operators, see, e.g., Gesztesy and Makarov [10], Lunyov and Malamud [21], Malamud and Neidhardt [23], see also the references therein. The fundamental matrix uniquely determines coefficients of the first order differential systems, see Malamud [22].…”
Section: Resultsmentioning
confidence: 99%
“…There are many results about the determinants for different classes of operators, see, e.g., Gesztesy and Makarov [10], Lunyov and Malamud [21], Malamud and Neidhardt [23], see also the references therein. The fundamental matrix uniquely determines coefficients of the first order differential systems, see Malamud [22].…”
Section: Resultsmentioning
confidence: 99%
“…Proof. (i) Due to [26,Proposition 5.9] the system of root functions of the operator L forms a Riesz basis with parentheses in L 2 ([0, 1]; C 2 ), where each block is constituted by the root subspaces corresponding to the eigenvalues of L that are mutually ε-close with respect to the sequence Ψ := {−ϕ 1 , −ϕ 2 , π − ϕ 1 , π − ϕ 2 }. Here ϕ j = arg b j , j ∈ {1, 2}, and ε > 0 is sufficiently small.…”
Section: )mentioning
confidence: 99%
“…In the recent paper [26] it was established the Riesz basis property with parentheses for system (1.1) subject to various classes of boundary conditions with a potential Q(·) ∈ L ∞ ([0, 1]; C n×n ).…”
Section: Introductionmentioning
confidence: 99%
“…The recent publications [17]- [20] devoted to the questions of completeness and spectral synthesis for general nn  first order systems of ODE (see also references therein). In [17], [18], [20] it was shown that the completeness property for some classes of boundary conditions essentially depends on boundary values of the potential matrix and explicit conditions of the completeness were found. In particular, in [20], an example of incomplete dissipative 22  Dirac operator was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in [20], an example of incomplete dissipative 22  Dirac operator was constructed. It was shown in [18], [19] that the resolvent of any complete dissipative Dirac type operator admits the spectral synthesis. Moreover, explicit conditions of the dissipativity and completeness of such operators were found.…”
Section: Introductionmentioning
confidence: 99%